Young men’s barriers to and facilitators of utilising HIV-testing services in South Africa - Sithembiso M.S. Ndlovu; Andrew Ross; James Ndirangu (Southern African Journal of HIV Medicine)
Background: In South Africa, men are less likely than women to use HIV-testing services (HTS). They are also unlikely to start and adhere to antiretroviral therapy until the virus has progressed to advanced AIDS stages.